Agile Processes in Software Engineering and Extreme Programming 18th International Conference, XP 2017, Cologne, Germany, May 22-26, 2017, Proceedings - Baumeister, Hubert; Lichter, Horst; Riebisch, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY license. The volume constitutes the proceedings of the 18th International Conference on Agile Software Development, XP 2017, held in Cologne, Germany, in May 2017. The 14 full and 6 short papers presented in this volume were carefully reviewed and selected from 46 submissions. They were organized in topical sections named: improving agile processes; agile in organization; and safety critical software. In addition, the volume contains 3 doctoral symposium papers (from 4 papers submitted). .
Improving Agile Processes -- Reflection in Agile Retrospectives -- What influences the speed of prototyping? An empirical investigation of twenty software startups -- Key Challenges in Agile Requirements Engineering -- A Multiple Case Study on Selecting a Technique for User-Interaction Data Collecting -- Comparing Requirements Decomposition within the Scrum, Scrum with Kanban, XP, and Banana Development Processes -- Effects of Technical Debt Awareness: A classroom study -- Agile in Organizations -- Don$1 (Bt Forget to Breathe: A Controlled Trial of Mindfulness Practices in Agile Project Teams -- Enhancing Agile Team Collaboration through the use of Large Digital Multi-touch Cardwalls -- Knowledge Sharing in a Large Agile Organisation: A Survey Study -- Teaching Agile Methods to Software Engineering Professionals: 10 Years, 1000 Release Plans -- Are Software Startups Applying Agile? the State of the Practice from a Large Survey -- Adopting Test Automation on Agile Development Projects: A Grounded TheoryStudy of Indian Software Organizations -- Safety Critical Software -- How is security testing done in agile teams? A cross-case analysis of four software teams -- An assessment of avionics software development practice: justifications for an agile development process -- Short Research Papers -- Inoculating an Agile Company with User-Centred Design: an Empirical Study -- On the Usage and Benefits of Agile Methods & Practices -- Checklists to Support Test Charter Design in Exploratory Testing -- Discovering Software Process Deviations Using Visualizations -- Exploring Workflow Mechanisms and Task Allocation Strategies in Agile Software Teams -- Are daily stand-up meetings valuable? A survey of developers in software teams -- Doctoral Symposium Papers -- Knowledge Management and Reflective Practice in Daily Stand-up and Retrospective Meetings -- Self-Assignment: Task Allocation Practice in Agile Software Development -- Software Development Practices Patterns. .s
Keywords: Software engineering; Software engineering -- Management; Electronic data processing -- Management; Software Engineering; Software Management; IT Operations